A great reckoning [large type] - Penny, Louise (Penny, Louise. Three Pines mystery., 2016)
"An intricate old map is found stuffed into a wall of the bistro in Three Pines, and the closer the villagers look, the stranger it becomes. Given to Armand Gamache as a gift the first day of his new job, the map eventually leads him to shattering secrets. To an old friend and older adversary. It leads the former Chief of Homicide for the Sûreté du Québec to places even he is afraid to go. But must. And there he finds four young cadets in the Sûreté Academy, and a dead professor. And, with the body, a copy of the old, odd map. Everywhere Gamache turns, he sees Amelia Choquet, one of the cadets. For both Choquet and Gamache, the time has come for a great reckoning." -- Back cover.